STRATEGI PERANAN KESENIAN TRADISIONAL DI KOTOTINGGI DALAM MENUNJANG INDUSTRI KREATIF: MELALUI MANAJEMEN PARIWISATA - Nursyirwan (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
ABSTRACT those two domains inspires us to rise up the Village of Kototinggi which has various talents. Therefore, in the matter of actualizing Creative Industry program, the final aim of the program Traditional artists should be placed as business partner of tourism, not a worker of it who should obey and bow to tourism management, but they are expected to be able collaborating with the tourism instead. The exploitation of tourism operator or worker must soon be stopped due to the dense of visitation of international visitors who wish to closely see the uniqueness, speciality and high valuable of its arts and traditional cultures. The contribution of Creative Industry program in the future is to prepare Kototinggi society to be ready in collaboration with tourism department as a partner of art college: Indonesia Art Institute of Padangpanjang